Effectiveness of Rehabilitation of Former Limestone Quarry Land: A Case of Ecologi-cal Market in Gari Village, Gunung Kidul Regency - Paska Prasasti Sinukaban; Dyah Tyahyandari Suryanuingtyas; Nuva Nuva (Green Publisher Indonesia, 2024)
The objective of the study was to evaluate the environmental, economic and social benefits of the reclamation of limestone from the quarry to pasar ekologis. Community involvement in reclamation planning is one of the government's strategies to accommodate the community's aspirations for the type of reclamation so that a sense of concern for the maintenance of Pasar Ekologis Argo Wijil can be properly carried out. The research was carried out in Gari Village, Gunung Kidul Regency. Data was collected through direct observation to measure plant height, observe the growth of vegetation in Pasar Ekologis Argo Wijil, and interview structures with traders and visitors. Pasar Ekologis Argo Wijil contains several plant species, including Terminalia mantaly, Pterocarpus indicus, Syzygium Mytifolium, and Tamarindus indica. Plant growth can be beneficial in pasar ekologis as it helps to reduce air pollution, ensuring safe activities can take place. The success of the reclamation of ex-mining limestone cannot be separated from the participation of the people of Gari Village. The community of Pasar Ekologis Argo Wijil has taken the initiative to increase green open spaces and promote vegetation growth by planting and replenishing more plants. The management of the pasar ekologis is enriched by the combination of traditional market culture and ecological concepts. Pasar ekologis was originally planned for Sunday mornings only. Activities in Pasar Ekologis Argo Wijil provide an opportunity for the community to improve the local economy. The reclamation of ex-mining limestone for a traditional market with an ecological concept promotes environmentally responsible behaviour.